‘Misclassified Partnership’ and the Impact of Legal Loophole on Workers - Nabiyla Risfa Izzati; Mas Muhammad Gibran Sesunan (BESTUUR, 2022)
In Indonesia, the partnership model was previously popularized by gig companies. However, now it is spreading into various businesses, such as e-commerce, shipping, and start-up industries. Over the years, the extensive use of the partnership model is becoming problematic as it transforms into a "misclassified partnership," where a job that should be considered an employment relationship is instead misclassified into a partnership. This study uses doctrinal legal research completed with a statutory approach to finding an apparent legal loophole regarding the partnership model within Indonesia's regulatory space. The term "partnership" is not recognized by Manpower Law. Micro, Small, and Medium Enterprises Law, on the other hand, identifies the term partnership (kemitraan) but does not contextualize it within the current partnership model. The research also found that this legal loophole has been impacting the working conditions of workers under the partnership model, robbing their workers' rights and legal protection by law. The possible solutions to the issue are then discussed by looking at the good practices in other countries, such as the UK, France, Spain, and the US